Overlapping but distinct roles for NOTCH receptors in human cardiovascular disease. Issue 1 (10th June 2018) - Meester, J.A.N.; Verstraeten, A.; Alaerts, M.; Schepers, D.; Van Laer, L.; Loeys, B.L.
Abstract : The NOTCH signalling pathway is an essential pathway, involved in many cellular processes, including cell fate decision, cell proliferation, and cell death and important in the development of most organs. Mutations in genes encoding components of the NOTCH signalling pathway lead to a spectrum of congenital disorders. Over the past decades, mutations in human NOTCH signalling genes have been identified in several diseases with cardiovascular involvement. NOTCH1 mutations have been described in bicuspid aortic valve disease, left‐sided congenital heart disease, and Adams‐Oliver syndrome. NOTCH2 mutations lead to the development of Alagille syndrome, while mutations in NOTCH3 cause cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy. To date, mutations in NOTCH4 have not been associated with cardiovascular disease. This review focuses on the mutations described in NOTCH1, NOTCH2, and NOTCH3 and their associated cardiovascular phenotypes. Abstract :